Phenotypic, antioxidant and physiological response of citrus japonica (Kumquat) leaves exposed to Xanthomonas citri subsp. citri - Olivella, Laura; Bustos, Dolores Angela; Alisio, Mauro; Reyes, Marcos; Céccoli, Gabriel; Derita, Marcos; Daurelio, Lucas (2024)
Poster